2022
DOI: 10.1021/acs.est.2c00706
|View full text |Cite
|
Sign up to set email alerts
|

Rational Regulation of Co–N–C Coordination for High-Efficiency Generation of 1O2 toward Nearly 100% Selective Degradation of Organic Pollutants

Abstract: Single oxygen-based advanced oxidation processes (1O2-AOPs) exhibit great prospects in selective degradation of organic pollutants. However, efficient production of 1O2 via tailored design of catalysts to achieve selective oxidation of contaminants remains challenging. Herein, we develop a simple strategy to regulate the components and coordination of Co–N–C catalysts at the atomic level by adjusting the Zn/Co ratio of bimetallic zeolitic imidazolate frameworks (Zn x Co1-ZIFs). Zn4Co1–C demonstrates 98% select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(69 citation statements)
references
References 65 publications
(103 reference statements)
2
60
0
Order By: Relevance
“…36 The appearance of (111) and (220) planes with the standard Co pattern at 45°and 51°, respectively, potentially suggests a face-centered cubic Fm3m structure of Co nanoclusters with 5.668 Å lattice parameters. 34,37 These results confirmed the preferential growth of Co nanoclusters along the (111) direction to anchor on the N-C biochar support. As mentioned above, the intensity ratio of the D to G bands functions as a direct indicator of the level of atomic ordering of carbonaceous materials, which would gradually increase with an increase in the relative degree of graphitization in amorphous biochar frameworks.…”
Section: Structural Insights Into Anchoring Co Clusters On N-doped Ca...supporting
confidence: 64%
“…36 The appearance of (111) and (220) planes with the standard Co pattern at 45°and 51°, respectively, potentially suggests a face-centered cubic Fm3m structure of Co nanoclusters with 5.668 Å lattice parameters. 34,37 These results confirmed the preferential growth of Co nanoclusters along the (111) direction to anchor on the N-C biochar support. As mentioned above, the intensity ratio of the D to G bands functions as a direct indicator of the level of atomic ordering of carbonaceous materials, which would gradually increase with an increase in the relative degree of graphitization in amorphous biochar frameworks.…”
Section: Structural Insights Into Anchoring Co Clusters On N-doped Ca...supporting
confidence: 64%
“…The optimized models of Co/NC@mSiO 2 (Figure S19) and Co/mSiO 2 (Figure S20) were proposed according to the previous XAFS and XPS results. Generally, PMS activation on the surface of catalysts consisted of two continuous steps: the adsorption toward O sites of PMS and then activation for ROS production . First, we examined the adsorption of PMS on the catalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…The N 1s spectrum of Co/ NC@mSiO 2 (Figure 2j) showed characteristic peaks of pyridinic N (or Co−N), pyrrolic N, graphitic N, and Noxide centered at 399.1, 400.4, 401.6, and 403.0 eV, respectively. 31 In contrast, no signals for the N element were detected in Co/mSiO 2 , further indicating that the presence of CTAB had an important impact on the formation of NC dots. The obvious changes in the C 1s and N 1s spectra proved the improved electronic structures of Co/NC@mSiO 2 due to the SMSI effect.…”
Section: Synthesis and Characterization Of The Catalystmentioning
confidence: 99%
“…However, when TBA with the molar ratio of TBA/PMS = 1000 was added, the k″ decreased to 0.0523 min –1 , indicating that · OH made little contribution to the degradation of BPA, while SO 4 ·– played a dominant role. In addition, l -histidine (L-HIS) and potassium dichromate (K 2 Cr 2 O 7 ) were selected as scavengers to verify the contribution of 1 O 2 and e – in the BPA degradation process. In order to eliminate the interference of SO 4 ·– and · OH, MeOH was also added into the degradation system. The results indicated that the contributions of 1 O 2 and e – to BPA degradation were limited.…”
Section: Results and Discussionmentioning
confidence: 99%